Clinical Case of Pulmonary Hypertension Secondary to Chronic Obstructive Pulmonary Disease in the Patient with History of Pulmonary Tuberculosis - M. V. Moiseeva; N. V. Bagisheva; I. A. Viktorova; A. V. Mordyk (Туберкулез и болезни лёгких)
The article describes the follow-up over a clinical case of the patient with COPD, pulmonary hypertension (PH), and history of pulmonary tuberculosis. According to the guidelines, treatment of the patient with PH which developed due to bronchopulmonary pathology was focused on constant bronchodilator therapy to reduce hypoxemia and to achieve additional vasodilating effect on vessels of the pulmonary circulation, as well as on non-invasive high-flow oxygen therapy which inhibited the progression of PH (it prevented mortality).